’Publish or Perish !’ - A Friend or a Foe for Author? - Karkii, Binod (Medical Journal of Shree Birendra Hospital, 2017)
Writing has always fascinated human beings! Be it the stone carving of ancient Greek history or the hand-written manuscripts of medieval times, they always show the existence of the writer. It shows that somebody has hunted the giant mammoth or how the ancient sculpture was built. In other words, we remember them. “Publish or perish!” has always been taken as a pressure in the academia to continuously publish ones’ work in the journals. This sometimes can have negative impact of submitting poor quality articles to the journals. The same can sometimes deviate oneself from the actual research agenda and lead to many unethical behaviors such as plagiarism and fabrication. The teaching capabilities of a certain individual in an institution can sometimes get overshadowed by his inability to publish on time. An institute nowadays may hire a teacher looking at the number of articles he has published rather than his intrinsic ability to make his pupils understand the profoundness of certain topic. Hence, some of them even consider this publish or perish as a tyranny in the field of literature. Nevertheless, publication is and will be an important pedestal for the progression of our scientific work. The truthfulness of our research is the responsibility of ourselves only. The intellectual theft will lead us nowhere other than the self-devaluation and remorse. There are certain rules and we all should follow them. Publication is the requirement of our academic progression; hence its importance cannot be undermined. Writing should begin from within oneself only. There is no age bar to learning hence the culture of writing in each one of us will eventually lessen the burden of gifted and ghost authors in our scientific society. Sharing of work amongst our peers and learning from each other will overcome the hindrance in publishing our work and so does the regular conduction of workshops and seminars for sensitizing our authors. No work can be great work without mutual effort. The time has come for the authors and the editors to sit down for a cup of tea to remove prejudices from each other and aid each other. Happy writing !